APLIKASI ECO-ENZYME DAN PUPUK N ANORGANIK PADA PERTUMBUHAN DAN HASIL BROKOLI (Brassica oleracea Var. Italica) - Sitawati Sitawati; Ulfatul Rosyida Al Fikriyah; Ellis Nihayati; Dewi Ratih Rizki Damaiyanti (Universitas Tribhuwana Tunggadewi, 2026)
Annual market demand for broccoli (Brassica oleracea var. italica) continues to rise. Nevertheless, this increasing trend has not been matched by adequate production quality and quantity, which remain relatively low, thereby necessitating improved cultivation techniques. Currently, broccoli farming is still highly dependent on inorganic fertilizers to support optimal plant growth. Consequently, incorporating organic fertilizers is essential to minimize this reliance. This study aimed to evaluate the effects of applying eco-enzyme to reduce nitrogen fertilizer rates on broccoli yield and quality. The experiment was conducted in Tulungrejo, Bumiaji, Batu City, East Java, from May to July 2024. A randomized complete block design (RCBD) with factorial arrangement was employed, consisting of two factors: eco-enzyme concentrations (0, 15, 30, and 45 ml L?¹) and synthetic N fertilizer rates (0%, 33%, 66%, 100%, and 133% of the recommended dose of 300 kg ha?¹). The results revealed a significant interaction between eco-enzyme concentration and synthetic N fertilizer rate. The application of 30 ml L?¹ eco-enzyme combined with a 66% reduction in inorganic N fertilizer notably enhanced leaf area (4.26%), flower diameter (18.48%), total fresh weight (50.14%), and edible fresh weight (43.82%) compared to the control. These findings suggest that eco-enzymes can effectively reduce dependence on inorganic nitrogen fertilizers in broccoli cultivation.